Study of Longitudinal Electron Scattering Form Factors with the Radial Wave functions of Transformed Harmonic-Oscillator for some Light Nuclei - Ridha, Arkan R.; Abood, Ali K. (Iraqi Journal of Science, 2025)
The wave functions of converted harmonic-oscillator in local scaling transformations are employed to evaluate charge distributions and elastic charge electron scattering form structures for 6,7Li, 9Be, 14,15N and 16O nuclei. The nuclear shell-model was fulfilled using Warburton-Brown  psd-shell (WBP) interaction with  truncation in  model space. Very good agreements with the experimental data were obtained for the aforementioned quantities.